PEMAKNAAN AGAMA DAN BUDAYA SAINTIFIK DALAM PEMBELAJARAN KURIKULUM 2013 - Ali, M. Makhrus (Universitas Islam Negeri Raden Intan Lampung, 2018)
This article wants to show that the transformation of Islamic Education towards the process of Integration of science and religion is relevant and concerned for the future development of Islamic religious education. Agree with post positivism which argues that science is actually a condition with nterests. Science should not only be oriented to science, but it can be used to improve socio-cultural conditions that are unfair and inhuman. Reality as a subjective matter, constructed, interpreted and not found. The human being is a composer of the world, giving meaning to the world, not limited by natural law and having a construct of meaning. Whereas the scientific structure is based on daily knowledge, inductive, ideographic, interpretation, and not value free. The aim is to interpret the world, understand life, emphasize meaning and understanding.Keywords: Agama, Budaya Saintifik, Pendidikan Integratif, Kurikulum 2013